2019
DOI: 10.1039/c8cc10254f
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of indium from non-aqueous electrolytes

Abstract: Indium(iii) is electrodeposited from organic electrolytes, in which indium(i) occurs as an intermediate species, and disproportionates to indium(iii) and indium(0) in the form of nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…However, the particle sizes all remain small (<5 µm), reagents must be dried and the plating bath must be held at high temperatures of 130 °C. In addition, as we have also observed under these conditions, the formation of a black material containing reduced metal nanoparticles is possible (Figure B,C) . All of these current methods rely on a liquid bath where objects must be submerged; however, by removing the bath, the electrolyte salt mixture plates around the trapped phosphor particles with a higher probability of incorporation, leading to higher surface loadings and the option to use larger particles (Figure D).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the particle sizes all remain small (<5 µm), reagents must be dried and the plating bath must be held at high temperatures of 130 °C. In addition, as we have also observed under these conditions, the formation of a black material containing reduced metal nanoparticles is possible (Figure B,C) . All of these current methods rely on a liquid bath where objects must be submerged; however, by removing the bath, the electrolyte salt mixture plates around the trapped phosphor particles with a higher probability of incorporation, leading to higher surface loadings and the option to use larger particles (Figure D).…”
Section: Introductionmentioning
confidence: 77%
“…In addition, as we have also observed under these conditions, the formation of a black material containing reduced metal nanoparticles is possible ( Figure 1B,C). [23] All of these current methods rely on a liquid bath where objects must be submerged; however, by removing the bath, the electrolyte salt mixture plates around the trapped phosphor particles with a higher probability of incorporation, leading to higher surface loadings and the option to use larger particles ( Figure 1D). In addition, with exception to a recent article using plasma electrolytic oxidation of aluminum, [24] reports of electrochemical deposition of metal matrix/phosphor composites to date have been limited to large bandgap phosphors that require short wave (200-350 nm) excitation wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…While indium(I) has been identified in a number of studies, the existence of indium(II) has not been reported. 11,16,18,19 Therefore, this species was not considered in our study. Because of the presence of a nucleation loop in the red CV in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids, deep-eutectic solvents (DES) and several organic electrolytes are more promising alternatives, as they have high (electro)chemical and thermal stabilities, but operate at lower temperatures. 11,[14][15][16][17][18][19] They support metal deposition in a broad potential and temperature range. However, ionic liquids and DES often have high viscosities, which hampers ion transport towards the electrode, lowering achievable current densities and thus deposition rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation